Queen's Park Hotel, Trinidad - (:unkn) unknown (My University, 2010)
The Queen's Park Hotel, located in Port of Spain on the Southern side of the Queen's Park Savannah, was first opened in January 1895. The postcard shows a car driving past the Queen's Park Hotel and one parked opposite.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Hotels--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Wooden windows--Trinidad and Tobago; Fretwork; Historic buildings--Trinidad and Tobago; Historic hotels--Trinidad and Tobago; [1920]; Cities and towns--Trinidad and Tobago--Port of Spain; Trees--Trinidad and Tobago; Architecture--Trinidad and Tobago; Roads--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Fences--Trinidad and Tobago; Transportation--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)